Impacts of Leadership Styles, Rewards Recognition on Quantity Surveyors’ Job Satisfaction in Klang Valley - Mahazir, Mashanim; Wai Sing, Teng; Abdul Razak, Diyana Syafiqah (Journal of Emerging Technologies and Industrial Applications, 2024)
As a key professional in construction project, job dissatisfaction of quantity surveyors is currently a major concern. Factors including transformational leadership style, transactional leadership style, reward and recognition and their impacts on job satisfaction is significant in improving job satisfaction. This project is conducted to propose significant factors to improve job satisfaction of quantity surveyors working in Klang Valley. The sample of 150 professional and consultant quantity surveyors working in consultant firms and contracting firms Grade 7 is explored. Quantitative research methods are used, and data collected is analysed using SPSS software. Some of statistical analysis tests used are descriptive analysis, reliability test, linear regression analysis and multi-regression analysis. Results shown that all independent variables have significant and positive relationship with job satisfaction. Recognition is the strongest predictor of job satisfaction (B=0.531, p<.01) with 59% variance in job satisfaction. Current findings are aligned with previous findings. Some findings are in contrast due to insignificant relationship with job satisfaction.